Pengaruh Promosi di Media Sosial dan Electronic Word of Mouth Terhadap Keputusan Berkunjung pada Mahakam Lampion Garden Kota Samarinda - Nur Erika Novira Indah; Finna Fourqoniah; M. Fikry Aransyah (Indonesian Journal Publisher, 2021)
This researcher aims to determine whether promotions on social media and electronic word of mouth have a significant effect on the decision to visit the Mahakam Lampion Garden in Samarinda city. The independent variable used in this study is the promotion of social media (X1) and electronic word of mouth (X2), and the dependent variable in this study is the visit decision (Y). This research is a descriptive study with a quantitative approach. The sampling technique used was purposive sampling using the slovin formula and obtained 100 respondents using multiple linear regression analysis techniques. Promotion variabel in social media and visiting electronic word of mouth have a positive and significant effect on decisions.